2016
DOI: 10.1158/0008-5472.can-14-2611
|View full text |Cite
|
Sign up to set email alerts
|

Novel Morphologic and Genetic Analysis of Cancer Cells in a 3D Microenvironment Identifies STAT3 as a Regulator of Tumor Permeability Barrier Function

Abstract: Tumor permeability is a critical determinant of drug delivery and sensitivity, but systematic methods to identify factors that perform permeability barrier functions in the tumor microenvironment are not yet available. Multicellular tumor spheroids have become tractable in vitro models to study the impact of a three-dimensional (3D) environment on cellular behavior. In this study, we characterized the spheroid-forming potential of cancer cells and correlated the resulting spheroid morphologies with genetic inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 45 publications
(51 reference statements)
2
18
1
Order By: Relevance
“…Little is known about the role of the heat shock response with regards to the efficacy of thermal therapy for GBM, and no studies have examined the use of CNMTT or other nanoparticle-based thermal therapies in the context of induced expression of HSPs. Furthermore, few studies have used three dimensional cell cultures such as multicellular tumor spheroids, which may more closely mimic tumors in vivo 34 , to evaluate nanoparticle-based thermal therapy. Therefore, the purpose of this study was: (i) to evaluate the feasibility of using slow infusion techniques similar to CED to deliver CNTs into brain extracellular matrix (ECM)-mimicking phantoms; (ii) to determine the efficacy of CNMTT in comparison to conventional heat delivery in GBM cell lines and multicellular tumor spheroids; and (iii) to determine if CNMTT could overcome the protective effects of induction of the heat shock response prior to initiation of CNMTT.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the role of the heat shock response with regards to the efficacy of thermal therapy for GBM, and no studies have examined the use of CNMTT or other nanoparticle-based thermal therapies in the context of induced expression of HSPs. Furthermore, few studies have used three dimensional cell cultures such as multicellular tumor spheroids, which may more closely mimic tumors in vivo 34 , to evaluate nanoparticle-based thermal therapy. Therefore, the purpose of this study was: (i) to evaluate the feasibility of using slow infusion techniques similar to CED to deliver CNTs into brain extracellular matrix (ECM)-mimicking phantoms; (ii) to determine the efficacy of CNMTT in comparison to conventional heat delivery in GBM cell lines and multicellular tumor spheroids; and (iii) to determine if CNMTT could overcome the protective effects of induction of the heat shock response prior to initiation of CNMTT.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the microwell mimics the in vivo environment and contains CSC-secreted factors [32]. One recent study reported that round spheroids showed a signature of high mRNA expression for secreted molecules, which activate cell cycle-related signaling pathways and their downstream transcriptional regulators [33]. This finding supports the idea that the microwell is more effective at mimicking the in vivo environment by sharing the medium.…”
Section: Resultsmentioning
confidence: 65%
“…The resulting spheroids were classified into four distinct groups based on morphology as 'round', 'mass', 'aggregate' and 'none' (Fig. 1) (19). For further analysis, the 'round', 'mass', and 'aggregate' types were grouped into the category 'mass-forming group' for efficient statistical analysis.…”
Section: Evaluation Of 3d Cell Culturementioning
confidence: 99%
“…With regards to environmental comparison, typical cells in 3D have ~100% of their surface area exposed to other cells or matrix, whereas cells in 2D have ~50% of their surface area exposed to fluid, ~50% exposed to the flat culture Prediction of tumor response of rectal cancer cells via 3D cell culture and in vitro cytotoxicity assay before initiating preoperative chemoradiotherapy surface or intermediate, and very little surface area exposed to other cells. A previous data analysis of spheroid-based drug screening systems revealed that tumor spheroid size and morphology in a 3D culture system was associated with in vivo drug sensitivity (19). Previous studies demonstrated significantly increased resistance to radiation in tumor cells in 3D cell culture, in comparison with that of 2D culture (20,21).…”
Section: Introductionmentioning
confidence: 99%